Catalytic asymmetric hydrometallation of cyclobutenes with salicylaldehydes. Issue 1 (10th December 2021) - Goetzke, F. Wieland; Sidera, Mireia; Fletcher, Stephen P.
Abstract : Chiral, substituted cyclobutanes are common motifs in bioactive compounds and intermediates in organic synthesis but few asymmetric routes for their synthesis are known. Abstract : Chiral, substituted cyclobutanes are common motifs in bioactive compounds and intermediates in organic synthesis but few asymmetric routes for their synthesis are known. Herein we report the Rh-catalyzed asymmetric hydrometallation of a range of meso -cyclobutenes with salicylaldehydes. The ortho -phenolic group promotes hydroacylation and can be used as a handle for subsequent transformations. The reaction proceeds via asymmetric hydrometallation of the weakly activated cyclobutene, followed by a C–C bond forming reductive elimination. A prochiral, spirocyclic cyclobutene undergoes a highly regioselective hydroacylation. This report will likely inspire the development of other asymmetric addition reactions to cyclobutenes via hydrometallation pathways.